THE PORTUGUESE NATIONAL INVENTORY ON PLANT GENETIC RESOURCES 2018 - DEVELOPMENT AND STATUS - Rocha, Filomena (International Journal of Research -GRANTHAALAYAH, 2018)
Since the 1970s, Portugal has been endeavouring systematic and coordinated efforts for ex situ conservation of plant genetic resources. Portugal maintains in ex situ a large seed collection of cultivated species (cereals, fibres, grain legumes, vegetables), wild species (forages, MAP species), also national clone collections of olive, fruit trees and grapes. In 2011 the Portuguese National Genebank (BPGV) and ISOPLEXIS implemented the GRIN-Global platform, as provides the opportunity to increase data quality, to have long term sustainability for data curation, integrates all collections in one management system optimizing the costs and staff resources. Now, the main objective in Portugal is to implement the Grin Global Platform at the national level to consolidate its National Programme of Plant Genetic Resources (NPPGR) with all national partners directly involved in the conservation of PGR. The main objectives of this communication are: to demonstrate the valuable contribution of the Grin-Global platform to the NPPGR; discuss the development and status of the Portugal’s National Inventory 2018 in EURISCO, analyse the evolution of the amount of passport information in EURISCO from 2015 to 2018; to address the steps that are being taken in Portugal for the Implementation of the Grin-Global Platform at the national level.